The 24-hour movement behaviour compositions of children with and without impaired motor coordination: The Moves-UP project - Nils Swindell; Chelsea Starbuck; Siqi Jin; Harriet Barker; Gemma Thomas; Jimena Rueda-Hernandez; Catherine Crosby; Claire Barnes; Huw Summers; Gareth Stratton (PLoS ONE, 2025)
The 24-hour movement behaviours, including sleep, sedentary behaviour (SB), and moderate-to-vigorous physical activity (MVPA) are crucial for a child’s healthy growth and development. Yet, the full 24-hour movement behaviour composition has not been thoroughly explored in children with suspected Developmental Coordination Disorder (sDCD). The aim of this study was to compare the 24-hour movement behaviour compositions of children with sDCD to their typically developing (TD) peers and to assess the associations between movement behaviours and motor competence. Sixty-nine children (mean age 8.6 ±  1.6 years, 55% boys) wore a wrist-mounted accelerometers for seven consecutive days, completed a dynamic motor competence assessment and were screened for sDCD using the Developmental Coordination Disorder Questionnaire. Results of the compositional Isotemporal-substitution analysis indicated that children with sDCD spent less time in light physical activity (LPA) and MVPA and more time in SB compared to the TD group. No significant differences were observed during school or weekend periods. However, increasing MVPA in place of lower-intensity activities was associated with theoretical improvements in motor competence. The 24-hour movement behaviour profiles of children with sDCD identified in this study may have adverse implications for their future health and wellbeing, emphasising the need for targeted interventions, particularly during out-of-school hours.